Peran Relasi dalam Keluarga Poligami untuk Pencapaian Keluarga Sakinah - Muhammad Arifin; Agus Purnomo; Rohmah Maulidia (Institut Agama Islam Negeri Ponorogo, 2024)
In Law Number 8 of 2016 concerning Persons with Disabilities as a guideline for the 'Aisyiyah Ponorogoro Integrated Blind Orphanage in fulfilling the protection and fulfillment of the rights of children with disabilities. However, in its fulfillment there are still deficiencies, for example in the rights to public services in Article 19 Paragraphs 1 and 2. Researchers want to analyze further the pattern of protecting the rights of disabled children and how the rights of disabled children are fulfilled at the Aisyiyah Ponorogo Integrated Blind Orphanage by Legal Effectiveness Perspective. The aim of this research is to obtain a complete, clear and detailed picture of the pattern of protection and fulfillment and to describe the fulfillment of the rights of children with disabilities. This research uses an inductive qualitative approach and seen from the formulation of the problem proposed, this research shows that it is real, empirical and can be seen so that researchers can understand the nature of life and care at the 'Aisyiyah Ponorogo Integrated Blind Orphanage. This research is field research, data collection techniques through observation, interviews, documentation. The research results show that the pattern of protecting the rights of children with disabilities at the 'Aisyiyah Ponorogo Integrated Blind Orphanage is implemented in accordance with the understanding of the regulations of Law Number 8 of 2016 concerning Persons with Disabilities which includes the application of the law, law enforcement and implementation of the law. Fulfillment of the rights of children with disabilities is seen from legal effectiveness factors, the effective factors being the legal factors themselves, law enforcement and cultural factors. And what has not been effective are the facilities and community factors which should be fulfilled in accordance with Article 19 paragraphs 1 and 2 of the Law on Persons with Disabilities.